Legitimacy of Delegating Authority to Third Parties in Procurement Contracts via Private Power of Attorney - Muhammad Asyikin; La Ode, Muhamad Taufik (Jurist-Diction, 2026)
Legal certainty in government procurement contracts is essential to ensuring accountability in state budget use. This study examines a case involving issuance of an informal power of attorney by a service provider’s director to a third party not named in the main contract for a clean water infrastructure project in West Halmahera Regency. The research assesses the legal validity of such delegation and its implications for contractual relationships. Using a normative legal approach, the study applies qualitative analysis of statutory provisions, contract doctrines, and a case study. Findings indicate that a power of attorney granted to a third party without explicit reference in the principal contract lacks binding legal effect and does not establish a direct legal relationship with the government. Such practices risk state losses due to implementation beyond the agreed legal framework. The study recommends reinforcing technical regulations and legal oversight to prevent abuse and uphold legal certainty.